A Review on The Axis Tracking Used for Solar PV Application. Issue 1 (April 2021) - Singh, Amit Pratap; Yadav, Indresh
Abstract: Today, the world is facing an immense challenge, such as the energy crisis, and we know that only small quantities of fossil fuels are available and these will be lost after 35-40 years or their quantities will be very limited. Hence, to fulfil our energy demand, the right option is to use renewable energy. Renewable energy is various types like wind energy, biomass energy (such as ethanol), hydropower energy, solar energy, etc. But we use solar energy the most because this energy is installed at a very low cost. And also, many important factors affect solar PV power production. Out of these, the most important is the solar tracking system which achieves very high efficiency in comparison to fixed systems. This paper uses various types of tracking techniques like active tracking, passive tracking, and chronological tracking, and also a comparison with the different tracking is also discussed. From these discussions, one can select the tracking method adopted for a specific application.